Data-Based Planning In Vocational High School 1 Manado - Harry Mosey, Samuel; Sony Junus Lengkong, Jeffry; Junior Mongdong, Romi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to describe and analyze the data-driven planning process implemented at Vocational High School (SMK) Negeri 1 Manado. Using a qualitative case study approach, data were collected through observation, interviews, and documentation from February to April 2025. The study focuses on three main stages: data-based identification of educational problems, root cause reflection, and the improvement of school programs and activities. The findings reveal that SMK Negeri 1 Manado systematically conducts problem identification using Education Report Card data and other internal data, involving various stakeholders. The root cause reflection is conducted collectively and systematically using gap analysis and data triangulation methods. Program improvements are designed based on identification and reflection results, with specific goals and measurable indicators, which are then incorporated into the Annual Work Plan and School Activity and Budget Plan. These stages form a sustainable data-driven planning cycle supported by proactive leadership and a collaborative culture within the school. This study contributes as a best practice model of evidence-based educational planning for school quality improvement.